Sur Color Expression and Transition Sharp in Sur Colored Lambs of Karakul - B. S. Mamatov; E. I. Refatova (Research Parks Publishing LLC, 2022)
The article describes the data obtained on the skin surface of the Saribel plant type and the local population of red-colored karakul lambs on color expression and transition intensity.